The Influence of Knowledge, Attitudes, and Maternal Age on the Incidence of Stunting of Toddlers Aged 1-5 Years - Khadijah, Siti; Purnama Sari, Agus (Jurnal Kebidanan dan Kesehatan Tradisional, 2025)
Background: During the toddler stage, which is an important phase in human growth, the fulfillment of balanced nutrition is essential. With short height due to long-term malnutrition, stunting is a chronic nutritional problem that is influenced by socioeconomic factors, health, and maternal knowledge and conditions. This study aims to analyze and determine the influence of knowledge, attitudes, and maternal age on the incidence of stunting in the work area of the Sebengkok Health Center in 2024.  Methods: This research uses a quantitative design with a case-control approach and purposive sampling technique. The sample consists of 102 mothers with children aged 1 to 5 years. The instrument used is a closed questionnaire to assess the mothers' knowledge about stunting, which has been tested for validity (Pearson Product Moment) and reliability (Cronbach's Alpha) with valid and reliable results. Data analysis was conducted using the Chi-Square test to see the relationship between independent variables and the occurrence of stunting in toddlers.  Results: A total of 57 mothers have good knowledge and attitudes, whereas 45 mothers have less favorable ones. A total of 52 mothers is aged <20 or >35 years. The Chi-Square test shows a significant influence of knowledge (p=0.005; OR=3.43), maternal age (p=0.003; OR=0.27), and maternal attitudes (p=0.005; OR=3.43) on the incidence of stunting.  Conclusion: Knowledge, age, and maternal attitudes have a significant relationship with the incidence of stunting in toddlers in the working area of the Sebengkok Health Center, Tarakan. Efforts to improve these three factors are important in stunting prevention.